A Framework for Optimization of Double Layer Grids with Supporting Cables - Kaveh, Ali; Akbari, Milad (Periodica polytechnica. Civil engineering. Bauingenieurwesen, 2022)
Space structures are used when it is required to cover a large unpaved area such as sports stadiums, aircraft factories, bridges, etc. Weight minimization is important in optimizing space structures, having various advantages such as cost reduction, reduction of the deterioration, increasing the possibility of using larger spans, and easy transportation and installation process. The use of meta-heuristic algorithms, inspired by the physics laws of nature, allows us to optimize a variety of complex problems. In this paper, four structures with different spans with and without cables are examined. Optimization is performed using Enhanced Colliding Bodies Optimization (ECBO) and Vibrating Particles System (VPS) optimization algorithms. The optimization is aimed to minimize the weight and the mid-span deflection of the structures. The utilized methods are based on the optimization algorithms in MATLAB (MATrix LABoratory) programming and the SAP2000 (Structural Analysis Program 2000) finite element software. In this way, the results, obtained from the structural analysis in finite element software, are utilized by the optimization algorithms and the operation is repeated until the optimal weight is achieved. In all the investigated examples, the ECBO performed better than the VPS algorithm. The findings indicate that the addition of the cables, in addition of reducing the weight of the structures can reduce the mid-span deflection.